Pancasila Has the Ability to Improve Community, Nation, and State Life in the Twenty-First Century - Wen Lee, Cheng-; Ande, Taufiqquddin (Journal Research of Social Science, Economics, and Management, 2022)
The world was shocked by the uncertainty surrounding the end of the COVID-19 epidemic, which had an impact on socio-economic inequality that claimed lives, especially in Indonesia. Pancasila is the basis of the Unitary State of the Republic of Indonesia and is the philosophy and way of life of the Indonesian nation. The purpose of this research is to reflect the soul and personality of the Indonesian people, making them more resilient and creative in dealing with the COVID-19 pandemic and able to improve the life of society, nation and state. This study uses a literature study approach that collects various data and facts from several documents related to the research problem. Based on the results of research, national values, such as religious values, human values, and harmony values, can be used as guidelines for behavior and attitudes in dealing with difficulties in the COVID-19 area.